Karakteristik Pembakaran Difusi Campuran Biodiesel Minyak Jarak Pagar (Jathropha Curcas L) - Etanol/Metanol Pada Mini Glass Tube - Al Banjari, M. Arsad; Yuliati, Lilis; Sonief, Achmad As’ad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
Diffusion is a combustion which is performed on a diesel engine, biodiesel as a biofuel is used to replace fossil fuels. Many studies have looked at the effect of a mixture of biodiesel fuel-ethanolmethanol-diesel with different percentages in terms of engine performance and exhaust emissions, but have never done research on the characteristics of combustion and interface evaporation. This paper discusses how the comparison of the characteristics of the diffusion combustion mixture of biodiesel and biodiesel-ethanol-methanol in mini glass tube. The results showed that the use of biodieselethanol occurred many explosions flame and lift off than biodiesel-methanol. Biodiesel-ethanol evaporation interfaces tend to be flat because there were many explosions so that the liquid fuel out of the burner. The use of biodiesel-methanol flame produces more stable than biodiesel-ethanol.